Enhancing papermark’s brand awareness and profitability with a blue ocean strategy - Theresia Maria Septyas Nugraheni (Priviet Social Sciences Journal, 2026)
This study examines the brand awareness and identity of Papermark, a Jakarta-based creative stationery brand, and proposes strategies to strengthen its position in Indonesia’s stationery market. Although Papermark has grown steadily, its visibility, digital presence, and customer engagement remain limited compared to those of its emerging and established competitors. This study identifies the drivers of awareness, diagnoses gaps between internal brand intentions and consumer experiences, and formulates recommendations to support long-term development. A mixed-method approach was used. Quantitatively, an online survey was analyzed using descriptive statistics and reliability testing to capture the perceptions of product aesthetics, functionality, personalization, digital touchpoints, and brand recall. Qualitatively, structured interviews with internal stakeholders, loyal customers, and potential customers explored operational priorities, brand meaning, and customer discovery paths. The integration of both sources enables an assessment of the current performance. The findings indicate that Papermark is perceived positively in terms of product quality, design consistency, and lifestyle. However, awareness is constrained by weak digital engagement, limited community building, and the underutilization of social media. Many respondents discovered the brand through offline retail, bazaars, or word-of-mouth rather than through digital channels. Younger consumers particularly associate stationery brands with high online activity, interactive content, and collaborative campaigns. This study recommends a digital community-centered strategy: identity-led content curation, consistent posting cadence, collaboration with creative communities, user-generated content activation, and interactive engagement tactics. Strengthening storytelling, improving search visibility, and integrating online and offline touchpoints are also recommended to elevate visibility, reinforce perceived value, and build customer relationship